English Communication Challenges among Indonesian Entrepreneurs: A Sociolinguistic Case Study - Akfan, Sofyan Sukwara (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This research examines how Indonesian entrepreneurs use English, focusing on grammar, pronunciation, and vocabulary. As language plays a key role in communication, non-native speakers often adjust their speech based on their native language. This study employs a qualitative descriptive method, analyzing recorded interviews with 10 Indonesian entrepreneurs from diverse business sectors, including retail, services, and small-scale manufacturing. The findings reveal common grammatical errors, such as omitting plural markers (-s/-es), auxiliary verbs, and definite articles, which stem from structural differences between English and Indonesian. Pronunciation challenges include substituting the /v/ sound with /f/ and mispronouncing certain English phonemes. Additionally, vocabulary issues arise from direct translations from Indonesian, resulting in unnatural expressions. Entrepreneurs also engage in code-switching, switching between English and Indonesian to emphasize key ideas, express emotions, and navigate complex conversations. These patterns demonstrate the influence of the Indonesian language on English usage, emphasizing the need for targeted language training in grammar, pronunciation, and vocabulary. By addressing these challenges, educators and trainers can develop tailored strategies to help Indonesian entrepreneurs improve their English communication skills, enhancing their business interactions and opportunities in global markets.